GIS-based assessment of selective heavy metals and stable carbon isotopes in groundwater of Islamabad and Rawalpindi, Pakistan - Rana, Sidra Aman; Ali, Syeda Maria; Ashraf, Muhammad; Shah, Ashfaq Ahmad; Iqbal, Kanwar Muhammad Javed; Ullah, Wahid; Tariq, Muhammad Atiq Ur Rehman; Iqbal, Naveed; Akhtar, Nadia; Ulain, Qurrat (Frontiers in Environmental Science, 2022)
The present study was undertaken to apply a nuclear technique in conjunction with a classical monitoring tool to characterize the origin, fate, and behavior of metal pollutants in the groundwater of the Islamabad-Rawalpindi Metropolitan. GIS and multivariate statistical analysis were employed for groundwater vulnerability assessment and source apportionment. The findings of the present study advocated that the concentrations of pH, phosphates, Cu, Mn, and Zn were within the drinking water standards in the Twin Cities. The contents of As and F were well within the allowable range at almost all the points except one location. However, Fe and Pb contents were above the permissible limits. Statistical analysis revealed that trace metals were derived from both geogenic and anthropogenic emissions. Computed WQI based on heavy metals reveals that groundwater quality was poor in most of the study area due to elevated EC, TDS, Pb, Fe, As, and F values. The more depleted isotopic composition of 13C clearly gives clues about the aquifer’s vulnerability from miscellaneous sources such as domestic, urban, constructional, and agricultural sites and the dissolution of carbonate minerals. The present study strongly counsels for improved hygienic practices, water treatment, and the provision of safe water to the urban populace. The monitoring results will lead to remedial measures to improve water quality in the Twin Cities.